Exploring the impact of a medication adherence intervention on recovery and mental health outcomes: A secondary analysis of the MAT-PLUS pilot RCT - Kevin Wenzel; Julia Thomas; Jennifer Carrano; Jennifer Stidham; Marc Fishman (Drug and Alcohol Dependence Reports)
Background: Substance use disorders (SUDs) including opioid use disorder (OUD) and alcohol use disorder (AUD) contribute to significant morbidity and mortality in the United States. Pharmacotherapy treatment, including extended-release naltrexone (XR-NTX), is underutilized in large part due to poor treatment retention. The MAT-PLUS (Medication Adherence Therapy: Psychosocial Leverage Using a Significant other) intervention combines assertive outreach, significant other involvement, and low-barrier access to medicine to improve retention on XR-NTX, and has shown promising results in a pilot RCT. Methods: This report explored secondary outcomes from the MAT-PLUS pilot RCT (NCT03567356) to determine the impact of the intervention on recovery experience as measured by the Recovery Assessment Scale (RAS) and mental health indicators as measured by the patient health questionnaire- somatic, anxiety, depression scale (PHQ-SADS) on N = 41 participants. Results: A series of repeated measures mixed ANOVAs did not find evidence of an effect of the MAT-PLUS intervention on these outcomes. Although total RAS scores did not improve over time in either condition, an independent samples t-test at the post-intervention follow up suggested some evidence of a possible treatment effect on two subscales of the RAS: 1) Not being dominated by symptoms and 2) Goal and success orientation. Discussion: The results of this study suggest that mental health symptoms are attenuated during treatment, whether usual care or the MAT-PLUS intervention, but that recovery indicators did not improve with treatment. Approaches to SUD care, including the MAT-PLUS intervention, should be refined to target improvements in recovery capital in addition to focusing on symptom reduction.